APUNTES SOBRE LOS CONTRATOS ATÍPICOS O INNOMINADOS - Ugarte Vega Centeno, Máximo Alfredo (2010)
The contracts that consider object intellectual goods constitute, regularly, nameless or atypical contracts. It signifies that the majority of these contracts are not explicitly regular by the law. Nevertheless, as every contract, they are governed by the general principles that govern in contractual matter. Now well, one of these general principles that govern the contracts is the principle of autonomy of the will. This principle covers great importance inside the General Theory of the Contracts, and in Copyright contracts matter its importance is clearly perceptible, since one of the most important consequences of this principle consists of the possibility that the individuals celebrate conventions of any type, not yet regulated explicitly by the law. It is as well as serves of base for the existence of nameless contracts, like the contracts of franchise, factoring, know how and leasing or the contracts of spectacle and data processing.